Fetal distress and intrauterine resuscitation; "Even the best treatment failure when its use without proper scientific criteria and generalizes" - Lam Figueroa, Nelly (2015)
Acute fetal distress is a serious problem that occurs in about 15% of  pregnant women in labor, producing a high perinatal mortality or rreversible neurological damage if nothing is done on time. This is why pregnant women at risk of developing or carrying insufficient uteroplacental chronic degenerative diseases that alter their homeostasis should be monitored closely for signs of possible deterioration. One of the most dramatic changes in obstetrics has been the use of biophysical and biochemical assessment of fetal wellbeing parameters, allowing to identify the products of risk and guide treatment, thus achieving decrease perinatal problems. The use of electronic fetal monitoring to assess the state of the product at risk in the prenatal period through a test contraction, as well as intrapartum, because in most cases, uterine activity is the triggering factor fetal distress, when added to other causes or predisposing factors.